(untitled) (International Research in Economics and Finance, 2018)
One approach to analyzing inequality is to compare average economic choices from a classical theoretical framework. Another approach considers the impact of the formation of society, through statutes and institutions, on average economic outcomes. This paper studies the effects of slavery on black-white wealth inequality upon the emancipation of slaves in the US using historical data. The purpose of wealth has varied from over time. From an economics perspective, wealth is the accumulation of resources that have market value and can be liquidated for present and future consumption. This study proceeds based on the most measurable assumption: households reside in a country with a mixed economy of markets and social planning, such that they have an incentive to accumulate material wealth for intertemporal household consumption and social influence. Becker (1957) and Arrow (1972) developed the most general theories of wage discrimination and favoritism. Oaxaca (1973) and Blinder (1973) have mechanized their theories for empirical analysis. While their findings are insightful, they cannot be directly applied to studying wealth differences since wealth is a complex combination of wages and other variables. Finally, since unexplained differences in states that abolished slavery after the Civil War were 10 percent higher than unexplained effects in states that abolished slavery well before the Civil War and the magnitudes of the unexplained effects were similar over the long-run, we cannot reject the existence of a negatively bounded correlation between the duration of time from enslavement and the magnitude of unexplained differences in wealth. This research was funded in part by the National Science Foundation under Grant SES 0096414. I would like to thank John Ham, Richard Steckel, Randall Olsen, Bruce Weinberg, Audrey Light, Nori Hashimoto, James Peck, Patricia Reagan, Charles Kirwin, Rebecca Blank, Charles Betsey, Alvin Thornton, Leibert Morris, Maude Toussaint-Comeau, Simone Wegge, James Wilbanks, Thomas Maloney, and William Collins for their insightful comments. I would also like to thank participants in workshops and seminars at the Ohio State University, Howard University, University of Michigan, American Economic Association Summer Program and Pipeline Conferences, Western Economics Association International meetings, and Social Science History Association meetings. I would also like to thank James Curtis Sr, K D Curtis, Karen Curtis (deceased), Lariece Grant-Brown, Barbara Broadnax, Dwayne Broadnax, Rudy Broadnax, Zee Curtis-Grant, Raymond Tillery, Chris Cooper, Dr. K A Troy, Dr. H. Beecher Hicks, Reverend Charles Lewis, Reverend Cornelius Wheeler, Reverend James Lewis, Elder David Treadwell, Dr. Stephen Tucker and Roberta Tucker, Minister Charles Webb, Minister David Surles, and Elder Gregory Strong for their support. This draft is a revision of a November 2010 paper and August 2001 paper.